KAPASITAS PENGELOLA BUMDES MAJU BERSAMA DI BIDANG PARIWISATA DESA PEBAUN HILIR KECAMATAN KUANTAN MUDIK KABUPATEN KUANTAN SINGINGI - Michella Putri Firanti; Adianto Adianto (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2022)
Kuantan Singingi Regency has a tourist village located in Kuantan Mudik District, precisely in the village of Pebaun Hilir, namely the Tobek Pebaun Tourism Object. Tobek Pebaun itself is a tourist attraction consisting of 2 seasons, namely the Lake Season and the Rice Planting Season. This study aims to analyze the capacity of Bumdes managers to advance together in the tourism sector of Pebaun Hilir Village and the factors that hinder the capacity of Bumdes managers to advance together in the tourism sector of downstream Pebaun villages. This study uses the theory of Alimbudiono & Fidelis (2004) which uses indicators, namely: good experience, education according to work, skills according to task. This research uses qualitative research. The results show that the management capacity is not good and inefficient because the employees who manage the Tobek Pebaun tourism object do not have special expertise in the field of developing tourism objects, due to their educational background coming from different fields. and special guidance as a guidance and counseling service provided by experts or professionals in their field on how to develop tourism from local governments.